Global, regional, and national differences in the burden of refraction disorders among children, adolescents, and older adults: current trends and future projections - Qiheng Yuan; Longji Wang; Bianjin Sun; Siwen Chen; Yutong Kang; Yongliang Lou; Meiqin Zheng (BMC Public Health)
Abstract Background Refraction disorders (RD), which includes myopia, hyperopia, astigmatism, and presbyopia, is the leading cause of visual impairment worldwide. Uncorrected RD is the leading cause of moderate and severe vision loss. However, existing studies have only analyzed the burden of RD at the global level, lacking analysis at the national level and specific populations. This study used data from the 2021 Global Burden of Disease (GBD) report to analyze regional differences and trends in the burden of RD among children, adolescents, and the elderly at the national level. Methods GBD 2021 data were used to examine RD burden in these groups, exploring associations with the Socio-demographic Index (SDI) and analyzing inequality trends. Decomposition analysis was applied, frontier analysis identified potential burden reductions, and Bayesian Age-Period-Cohort (BAPC) Models were used to forecast future trends. Results From 1990 to 2021, RD cases increased from 21.48 million to 24.45 million (a 13.8% increase) in children and adolescents, and from 29.26 million to 60.82 million (an increase of 107.87%) in the elderly. Decomposition analysis also revealed that population growth was the primary driver of the increased RD burden in both age groups. In regions with Middle, High-middle, and High SDI, the estimated annual percentage change (EAPC) of Age-Standardized Prevalence Rate (ASPR) in children and adolescents was positive, indicating an upward trend in the burden of RD. RD burden differed by age and region: higher SDI regions had a heavier burden in children and adolescents, while lower-income countries faced a greater burden in the elderly. Health inequalities became more evident in children and adolescents, while slightly lessened in the elderly. Overall, the RD burden was higher in the elderly compared to children and adolescents. By 2030, global RD cases are projected to reach 24.21 million in children and adolescents and 79.70 million in the elderly (31.05% increase expected), with countries like India, China, Oman, Paraguay, and Congo facing significant challenges. In addition, countries such as India, Spain, Bangladesh and others pay special attention to the male burden. Conclusion The current RD burden is serious and requires targeted management strategies, especially in High SDI regions for children and adolescents and in Low-middle SDI regions for the elderly. The male burden in some high-burden areas cannot be ignored.